COLLABORATIVE GOVERNANCE FOR LEGAL PROTECTION OF THE NANAS BIKANG BANGKA SELATAN GEOGRAPHICAL INDICATION: SYNERGY AMONG LOCAL GOVERNMENT, MPIG, AND COMMUNITY ACTORS - Achmad Affandi; Rendi Saputrama; Prayuda Rizky Arfallah; Dwikki Ogi Dhaswara (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2026)
This study examines the collaborative governance in the legal protection of the Geographical Indication (GI) of Nanas Bikang Bangka Selatan, with a particular focus on the synergy among the Local Government, the Geographical Indication Protection Society (MPIG), and local farming communities. A qualitative case study approach was employed to investigate institutional dynamics, stakeholder roles, and the effectiveness of GI implementation through interviews, field observations, document analysis, and data triangulation. The results indicate that the unique physicochemical characteristics of Nanas Bikang including a high water content of 82.95%, total sugar level of 13.70%, and vitamin C content of 98.58 mg/kg are shaped by the distinct agro-ecological conditions of South Bangka, such as an annual rainfall of approximately 2,513 mm, an average temperature of 27.2°C, and sandy loam soil that promotes sugar accumulation and fruit tenderness. Institutionally, the MPIG has established a formal structure, cultivation SOPs, product origin codes, and internal monitoring mechanisms as essential requirements for GI protection. However, challenges remain in strengthening farmers’ technical capacity, ensuring consistent quality control, and improving post-harvest infrastructure. This study contributes novelty by integrating detailed laboratory–agro-ecological data with a comprehensive analysis of multi-actor collaborative governance, offering a model that can be replicated for GI development in Indonesia. The findings emphasize that GI success depends not only on legal registration but also on the effectiveness of inter-institutional collaboration and the consistent application of quality standards throughout the value chain.